2018
DOI: 10.1016/s1473-3099(18)30411-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ultra-sensitive malaria diagnosis versus standard molecular diagnostics for malaria elimination: an in-depth molecular community cross-sectional study

Abstract: Swiss National Science Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
129
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 97 publications
(135 citation statements)
references
References 30 publications
3
129
0
Order By: Relevance
“…The results here differ from other studies conducted in non-pregnant populations that showed a significant increase in sensitivity of the uRDT compared to current RDTs. [19,26,30,31]. The most apparent difference between the conflicting results is the target population (pregnant vs non-pregnant) and the storage conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The results here differ from other studies conducted in non-pregnant populations that showed a significant increase in sensitivity of the uRDT compared to current RDTs. [19,26,30,31]. The most apparent difference between the conflicting results is the target population (pregnant vs non-pregnant) and the storage conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A modelling study found that in such areas LLINs alone could not lead to interruption of P. vivax transmission and additional tools are required to accelerate to elimination [27]. Considering the abundance of low level parasitaemia, particularly in P. vivax infections as transmission is reduced, more sensitive diagnostic tools may need to be applied to monitor progress and species composition [28].…”
Section: Discussionmentioning
confidence: 99%
“…Das et al 9 reported a uRDT sensitivity of 44% (95% CI: 15-77%) and specificity of 99.8% (95% CI: 99-100%) compared with quantitative reverse transcriptase PCR (qRT-PCR) and compared with a sensitivity of 0% (95% CI: 0-37%) and a specificity of 100% (95% CI: 99-100%) for the cRDT (Bioline, Standard Diagnostics) in whole blood specimens collected from asymptomatic individuals in a cross-sectional survey in Myanmar, where the positivity was 1.8% (9 of 493) by qRT-PCR. An analysis of 247 blood samples from a cross-sectional survey in Papua New Guinea by Hofmann et al 12 reported a uRDT (Malaria Ag P.f Ultra-Sensitive, Standard Diagnostics) sensitivity of 27% compared with 15% for cRDTs (Malaria Ag P.f/P.v, Standard Diagnostics) with qPCR used as a reference method. It should be noted that the PCR techniques used differed between studies and may explain some of the differences in the results.…”
mentioning
confidence: 99%